Electromagnetic Superpotentials forthe Liénard - Wiechert Field - Barrera F., V.; López-Bonilla, J.; Sosa P., J. (Communications in Physics, 2009)
Weert deduced a superpotential for the bounded part of the Maxwell tensor \(T_{ab}\) $ associated to the Liénard-Wiechert field. In this work we explicitly construct the non-local superpotential for the radiative part of \(T_{ab}\)